Insights into grape-derived health benefits: a comprehensive overview - Marta Angela de Almeida Sousa Cruz; Monique de Barros Elias; Daniela Calina; Javad Sharifi-Rad; Anderson Junger Teodoro (Food Production, Processing and Nutrition, 2024)
Abstract Grapes, renowned for their diverse phytochemical composition, have long been recognized for their health-promoting properties. This narrative review aims to synthesize the current research on grapes, with a particular emphasis on their role in disease prevention and health enhancement through bioactive compounds. A comprehensive review of peer-reviewed studies, including in vitro, in vivo, and clinical investigations, was conducted to elucidate the relationship between grape consumption and health outcomes. The review highlights the positive association of grape intake with a decreased risk of chronic diseases such as cardiovascular disease, type 2 diabetes, and certain cancers. Notable bioactive components like resveratrol are emphasized for their neuroprotective and antioxidative capabilities. Additionally, the review explores emerging research on the impact of grapes on gut microbiota and its implications for metabolic health and immune function. This updated review underscores the importance of future research to fully leverage and understand the therapeutic potential of grape-derived compounds, aiming to refine dietary guidelines and functional food formulations. Further translational studies are expected to clarify the specific bioactive interactions and their impacts on health. Graphical Abstract